Analisis Pengaruh Distribusi dan Harga Terhadap Peningkatan Penjualan Produk - Devi Pertiwi Ananda Putri; Akhmad Sukardi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
Marketing in a company is a function that determines the company's success in making a profit. One activity that has an important role in marketing is the distribution of goods and services. Apart from that, determining prices is also important in increasing sales. The aim of this research is to determine the effect of distribution and price on increasing sales. This type of research is qualitative using a literature review method whose sources are obtained from the latest journals in the last 5 years. The results of this research are that distribution can increase product sales. Distribution plays an important role in determining the sales volume that a company can achieve. Price can influence increased sales. If the company is correct in determining the price of its product, it will have an impact on increasing sales of the product.